PENGEMBANGAN THREE TIER MULTIPLE CHOICE TEST PADA MATERI KESETIMBANGAN KIMIA MATA KULIAH KIMIA DASAR LANJUT - Pandu J Laksono (Chemistry Education Department of Education and Teaching Faculty, 2020)
This study aims to develop a three tier multiple choice test instrument on chemical equilibrium material to identify misconceptions in students. The development model used by Borg and Gall (1983): (1) research and data collection, (2) planning, (3) developing product drafts, (4) conducting initial field trials, (5) making revisions to initial products; (6) conducting limited field tests, (7) product improvement. This research was conducted with 60 respondents. Validation uses the Aiken method with 5 expert validators. The conclusion is that the three tier multiple choice test instrument developed was declared to be feasible and met the criteria as a good problem with the average aiken validity of 0.87. The instrument was declared feasible in terms of the reliability of the test 0.806 included in the high category, has a distinguishing power of 0.351 so that it was categorized as good. Difficulty level found 20% categorized as easy problems, 71.11% categorized as moderate and 8.89% categorized as difficult. Based on the deception index, it was concluded that the deception mostly worked better than the answer key and the deception value mostly more than 5% was chosen so that it was declared effective. Three Tier Multiple Choice Test instrument seen from the practicality included in good categories with a percentage of 78.28%.